Edomite Defectors Among the Israelites - Evidence from Psalm 124 - Amzallag, Nissim (Old Testament Essays, 2021)
The present analysis of Ps 124 suggests that it relates the retreat to Israel of a foreign group of YHWH’s worshipers. Its Edomite identity emerges from its comparison with other Songs of Ascents (especially Pss 120, 122 and 129) and the Adam appellation of their land of origin (v. 2). The setting of Ps 124 in complex antiphony provides further details concerning their fleeing from Edom, their new commitment to Israel, and their Edomite brothers’ angry reaction. These events corroborate other biblical sources aiming for the integration of a group of Edomite poets and singers in the Jerusalem temple at the early Persian period. The consequences concerning the nature of the corpus of Songs of Ascents are discussed. https://doi.org/10.17159/2312–3621/2021/v34n1a4